2021
DOI: 10.34172/jlms.2021.30
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Photobiomodulation and Vitamin D on Odontogenic Activity of Human Dental Pulp Stem Cells

Abstract: Introduction: The regeneration of dental pulp tissue using human dental pulp stem cells (HDPSCs) has attracted increasing attention in recent years. Recent studies have suggested that several factors such as photobiomodulation (PBM) and vitamin D affect the proliferation and differentiation of HDPSCs. Therefore, the present study evaluated the effects of PBM and vitamin D on odontogenic differentiation of HDPSCs for dentin -like tissue formation. Methods: HDPSCs were collected, isolated, and characterized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Despite that the laser energy used to study its effect on stem cell proliferation and differentiation in conjugation with pulp regeneration was ranged in the low energy fluencies levels of 1-7 J/cm 2 in which 5 J/cm 2 demonstrated the highest stimulative effect in short term evaluation (44,45) the total energy used for the present study was 27 J/cm 2 . This decision was owing to the fact of light energy attenuation by buccal bone and overlaying mucosa in contrary to previous preclinical studies.…”
Section: Discussionmentioning
confidence: 98%
“…Despite that the laser energy used to study its effect on stem cell proliferation and differentiation in conjugation with pulp regeneration was ranged in the low energy fluencies levels of 1-7 J/cm 2 in which 5 J/cm 2 demonstrated the highest stimulative effect in short term evaluation (44,45) the total energy used for the present study was 27 J/cm 2 . This decision was owing to the fact of light energy attenuation by buccal bone and overlaying mucosa in contrary to previous preclinical studies.…”
Section: Discussionmentioning
confidence: 98%
“…Collagen which forms approximately 90% of the dentin organic composition is made by the odontoblasts before being secreted into pre-dentin as a network of collagen fibers which later act as a scaffold for mineral crystals [16]. Fibronectin and tenascin may also play a role in dentin mineralization and in the ability of fibroblast differentiation to form mineralized tissue [15], [17].…”
Section: Discussionmentioning
confidence: 99%
“…More than 1 study assessed the outcomes of using PBM in conjunction with direct pulp capping [12], [13] and its effect on regeneration potential of dental pulp complex [14]. PBM elevates the secretion of certain proteins that are of high value in the dentin bridge formation cycle in addition to another set of proteins that signal the initiation of dentinogenesis [15], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, PBM in 980 nm wavelength has not been widely investigated compared to the lower wavelengths. A recent study demonstrated that PBM promotes the odontogenic differentiation and mineralization of dental pulp stem cells (DPSCs) (20). Given the aforementioned facts, PBM appears to be considered an appropriate candidate for enhancing osteo/odontogenic differentiation and the formation of mineralized tissue.…”
Section: Introductionmentioning
confidence: 99%